Dynamics of psychophysiological state of the boxers influenced by the standard of specialized demands of specialized basic training - Martsiv V.P (Kharkov National Pedagogical University, 2013)
Examined the psychophysiological state of boxers with 9 types of reactions to the anticipation stage of the specialized basic training. In the experiment involved 18 male boxers aged 18-20 years. We investigated the dynamics of the reactions of anticipation in boxers under the influence of standard specialized loads. In the main part of the session boxers improved individual series 4-5 shock the boxing bag with the installation of the most strongly and quickly strike (loading dose - 9 rounds of 3 minutes each with an interval of 1 minute rest). Upon completion of the boxers performed strength training with weightlifting neck and stuffed ball. The regularities of the occurrence of each type of response in this group of athletes, provides a way of their use as criteria for assessing the psycho-physiological state of boxers.